Economic assessment of bioethanol recovery using membrane distillation for food waste fermentation - Noor Intan Shafinas, Muhammad; Rosentrater, Kurt A. (MDPI AG, 2020)
Ethanol is a material that has a high demand from different industries such as fuel, beverages, and other industrial applications. Commonly, ethanol has been produced from yeast fermentation using sugar crops as a feedstock. However, food waste (FW) was found to be one of the promising resources to produce ethanol because it contained a higher amount of glucose. Generally, column distillation has been used to separate ethanol from the fermentation broth, but this operation is considered an energy-intensive process. On the contrary, membrane distillation is expected to be more practical and cost-effective because of its lower energy requirement. Therefore, this study aims to make a comparison of economic performance on FW fermentation with membrane distillation and a conventional distillation system using techno-economy analysis (TEA) method. A commercial-scale FW fermentation plant was modeled using SuperPro Designer V9.0 Modeling. Discounted cash flow analysis was employed to determine ethanol minimum selling price (MSP) for both distillation systems at 10% of the internal rate of return. Results from this analysis showed that membrane distillation has a higher MSP than a conventional process, $6.24 and $2.41 per gallon ($1.65 and $0.64 per liter) respectively. Hence, this study found that membrane distillation is not economical to be implemented in commercial-scale ethanol production.